Prevalence and determinants of double and triple burden of malnutrition among mother-child pairs in Malawi: a mapping and multilevel modelling study - Jessie Jane Khaki; Peter M Macharia; Lenka Beňová; Emanuele Giorgi; Aline Semaan (Cambridge University Press, 2024)
Abstract Objective: To establish the prevalence of double burden of malnutrition (DBM) and triple burden of malnutrition (TBM) among mother-child pairs in Malawi and explore their geographical distribution and associated multilevel factors. Design: Cross-sectional study using secondary data from the 2015-2016 Malawi Demographic and Health Survey using a mixed effects binomial model to identify multilevel factors associated with DBM and TBM. Georeferenced covariates were used to map the predicted prevalence of DBM and TBM. Setting: All twenty-eight districts in Malawi. Participants: Mother-child pairs with mothers aged 15-49 years and children aged below 60 months (n 4618 pairs) for DBM and between 6 and 59 months (n 4209 pairs) for TBM. Results: Approximately 5·5 % (95% confidence interval (CI): 4·7 %, 6·4 %) of mother-child pairs had DBM, and 3·1 % (95 % CI: 2·5 %, 4·0 %) had TBM. The subnational-level prevalence of DBM and TBM was highest in cities. The adjusted odds of DBM were threefold higher (adjusted Odds Ratio, AOR: 2·8, 95 % CI: 1·1, 7·3) with a higher proportion of wealthy households in a community. The adjusted odds of TBM were 60 % lower (AOR: 0·4; 95 % CI: 0·2, 0·8) among pairs where the women had some education compared with women with no education. Conclusions: Although the prevalence of DBM and TBM is currently low in Malawi, it is more prevalent in pairs with women with no education and in relatively wealthier communities. Targeted interventions should address both maternal overnutrition and child undernutrition in cities and these demographics.